TIME DELAY ANALYSIS USING CRITICAL PATH METHOD (CPM) (Case Study: Kerobokan Bali Parking Building Construction Project) - Putri, Dwi Cahyani; Witjaksana, Budi; Tjendani , Hanie Teki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Parking Building is a structure specifically built for vehicle parking. Kerobokan Bali Parking Building is one such structure that utilizes steel as its main material. With dimensions of 13.97 meters in height, 32.8 meters in width, and 16.18 meters in length, this building had a planned construction duration of 259 calendar days starting from July 2023. The parking building experienced delays due to flooding in the basement area, necessitating time acceleration analysis using the CPM method. This thesis employs the CPM method to identify critical path activities. Once the critical paths are identified, a crashing program analysis will be conducted, involving an alternative such as overtime work with a duration of 4 hours. Based on the analysis using the CPM method, it was found that 75 activities are critical, listed in Microsoft Project rows 368-369-370-372-380-381-382-383-384-385-387-388-389-390-392-393-394-395-398-399-400-402-403-404-406-412-415-416-417-419-420-421-422-424-425-426-427-428-430-431-432-433-435-436-437-438-441-442-443-445-471-472-473-475-476-477-479-526-527-528-530-535-621-628-629-630-633-634-635-638-639-640-643-644.